PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA EKOWISATA TAMAN AIR INDONESIA KABUPATEN BOYOLALI TAHUN 2013-2022 - Cahyani, Aisyah Nur; Purwanto, Hari; Dwi Pratiwi, Yunita Niqrisah; Triatmaja, Nur Asih; Wulandari, Amy (EKOBIS, 2024)
The primary aim of a company is to achieve a specific level of profitability. Profitability encompasses different ratios, but this study specifically focuses on the ROA (Return On Assets) ratio, which is calculated by dividing net income by total assets. The objective is to determine the profit percentage generated by the company during a specified period. This research seeks to assess the effects of cash flow, accounts receivable management, and inventory management on the profitability of Ecotourism at the Indonesian Water Park in Boyolali Regency from 2013 to 2022. The sampling technique utilized in this study is purposive sampling, which involves selecting samples based on specific criteria. The data considered will be the financial statements of the company. The findings of the study suggest that cash flow and inventory management do not exert significant influence on profitability. However, when examined collectively, cash flow, accounts receivable management, and inventory management collectively affect the profitability of Ecotourism at the Indonesian Water Park in Boyolali Regency.